Analysis of isolates from Bangladesh highlights multiple ways to carry resistance genes in Salmonella Typhi - Lima, Nicholas Costa Barroso (BMC Genomics, 2019)
BACKGROUND: Typhoid fever, caused by Salmonella Typhi, follows a fecal-oral transmission route and is a major global public health concern, especially in developing countries like Bangladesh. Increasing emergence of antimicrobial resistance (AMR) is a serious issue; the list of treatments for typhoid fever is ever-decreasing. In addition to IncHI1-type plasmids, Salmonella genomic island (SGI) 11 has been reported to carry AMR genes. Although reports suggest a recent reduction in multidrug resistance (MDR) in the Indian subcontinent, the corresponding genomic changes in the background are unknown. RESULTS: Here, we assembled and annotated complete closed chromosomes and plasmids for 73 S. Typhi isolates using short-length Illumina reads. S. Typhi had an open pan-genome, and the core genome was smaller than previously reported. Considering AMR genes, we identified five variants of SGI11, including the previously reported reference sequence. Five plasmids were identified, including the new plasmids pK91 and pK43; pK43and pHCM2 were not related to AMR. The pHCM1, pPRJEB21992 and pK91 plasmids carried AMR genes and, along with the SGI11 variants, were responsible for resistance phenotypes. pK91 also contained qnr genes, conferred high ciprofloxacin resistance and was related to the H58-sublineage Bdq, which shows the same phenotype. The presence of plasmids (pHCM1 and pK91) and SGI11 were linked to two H58-lineages, Ia and Bd. Loss of plasmids and integration of resistance genes in genomic islands could contribute to the fitness advantage of lineage Ia isolates. CONCLUSIONS: Such events may explain why lineage Ia is globally widespread, while the Bd lineage is locally restricted. Further studies are required to understand how these S. Typhi AMR elements spread and generate new variants. Preventive measures such as vaccination programs should also be considered in endemic countries; such initiatives could potentially reduce the spread of AMR. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5916-6) contains supplementary material, which is available to authorized users.